2018
DOI: 10.1002/adfm.201800938
|View full text |Cite
|
Sign up to set email alerts
|

Are Electrospun Fibrous Membranes Relevant Electrode Materials for Li‐Ion Batteries? The Case of the C/Ge/GeO2 Composite Fibers

Abstract: Self-supporting paper-like membranes consisting of carbon/germanium dioxide (C/GeO 2 ) fibers are prepared via electrospinning of solutions with different germanium load (2.50−4.25 wt%), followed by carbonization at 550−700 °C, and are evaluated as anode materials in lithium ion batteries. The investigation of the physicochemical properties of the membranes by several characterization techniques shows that, as expected, with increasing carbonization temperature better graphitized and less nitrogen-rich C fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
(237 reference statements)
0
14
0
Order By: Relevance
“…At last, a single-step (calcination) or multi-step post-spinning heat treatment (stabilization and carbonization, sometimes followed by activation) upon different atmospheres (air, inert gases, gas mixture, activating gases) can be necessary to finalize the production process of the various fiber typologies (Figure 3). Polymer fibers do not require any treatment [46,47]; pure (and doped) oxide fibers are obtained by removing the organic component of the precursor(s) via an oxidative process [48][49][50][51], whereas stabilization of the polymer enabling its subsequent processing at higher temperature for graphitization is needed to obtain carbon and composite carbon-based fibers [52][53][54][55][56][57][58]. Activation upon gaseous atmosphere [53] or chemical etching to remove sacrificial templating agents [59] are utilized to enhance the fiber porosity and surface area.…”
Section: Appl Sci 2018 8 X For Peer Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…At last, a single-step (calcination) or multi-step post-spinning heat treatment (stabilization and carbonization, sometimes followed by activation) upon different atmospheres (air, inert gases, gas mixture, activating gases) can be necessary to finalize the production process of the various fiber typologies (Figure 3). Polymer fibers do not require any treatment [46,47]; pure (and doped) oxide fibers are obtained by removing the organic component of the precursor(s) via an oxidative process [48][49][50][51], whereas stabilization of the polymer enabling its subsequent processing at higher temperature for graphitization is needed to obtain carbon and composite carbon-based fibers [52][53][54][55][56][57][58]. Activation upon gaseous atmosphere [53] or chemical etching to remove sacrificial templating agents [59] are utilized to enhance the fiber porosity and surface area.…”
Section: Appl Sci 2018 8 X For Peer Reviewmentioning
confidence: 99%
“…It is widely recognized that carbon incorporation and nano-sizing improve the electrochemical and mechanical performance of the electrode materials [72,[76][77][78][79], providing them with enhanced electronic conductivity and increased resistance against the large volume changes, from which they suffer during the lithiation/de-lithiation process. It has been further shown that the use of binder-free self-supporting flexible carbon-based membranes as electrode materials [56][57][58]66,[80][81][82][83][84] translates into a beneficial reduction of the inactive weights with a consequent gain in the effective gravimetric and volumetric capacities of the batteries. These benefits are of crucial importance in manifold applications including transportation, aerospace, and portable and wearable electronics.…”
Section: Appl Sci 2018 8mentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐supporting paper‐like membranes consisting of C/Ge dioxide (C/GeO 2 ) fibers are prepared via electrospinning of PAN/DMF/Ge(OCH(CH 3 ) 2 ) 4 germanium(IV) isopropoxide gel solutions with different Ge load (2.50–4.25 wt%), followed by carbonization at 550–700 °C. The membrane anode prepared from solution with 4.25 wt% Ge‐load by cold‐pressing and carbonization at 700 °C delivered about 1500 mAh cm −3 after 50 cycles at 50 mA g −1 with a Coulombic efficiency close to 100% . 3D interconnected Ge/C‐NCFs composites were prepared by annealing GeO 2 ‐polyvinyl alcohol (PVA) gel at 800 °C for 5 h, GeO 2 ‐PVA gel be coated onto NCFs surface through steeping the NCFs into the above gel solution.…”
Section: Preparation Of Ge Anodesmentioning
confidence: 99%
“…This enhance capacity performance can be attribute to the following the catalytic effect of Ge and promoting the decomposition of Li 2 O, which also enables to improve the conversion reaction of GeO 2 . C/Ge/GeO 2 composite fibers were prepared via electrospinning of solutions with different Ge load (2.50–4.25 wt%), followed by carbonization at 550–700 °C . With increasing carbonization temperature better graphitized and less N rich carbon fibers were obtained, containing Ge 0 and/or reduced oxide phases along with GeO 2 NPs, combined with the cold pressing of the as‐spun membrane that the hollow space within the fibers had been noticeably reduced to rise more compact and tight structure, C/Ge/GeO 2 composite fibers showed initial discharge volumetric capacities of 1390–3580 mAh cm −3 .…”
Section: Enhanced Electrochemical Performances Of Ge For Libsmentioning
confidence: 99%